'68 beyond the Boreal Springs: Public representations of Brazilian university students in action - José Luis Hernández Huerta (Arizona State University, 2018)
The student movements which took place worldwide during 1968 had a considerable impact in Brazil, where they emerged as one of the social groups at the forefront of civic resistance to the dictatorship and modernisation of the university system. This article discusses the representations of Brazilian students in action, constructed and disseminated in the public sphere by the daily press. Particular attention is paid to (1) the motives, demands and aspirations of the activist student youth, (2) their capacity for social mobilisation, integration of alternative political figures and negotiation with the State, (3) the places, times and intensities of their actions, and (4) the narratives constructed by the daily newspapers on the basis of the testimonies, opinions and interests of the journalists, the protagonists of the movement and the rest of the social actors involved in the student issues of the day. The period of time selected for examination runs from the Seventh-Day Mass (marking the end of the events surrounding the death of Edson Luís de Lima Souto at the Calabouço Restaurant), and the Passeata dos Cem Mil (March of the One Hundred Thousand), which can be considered the turning point in the events which led to the passing of AI-5 - the repressive military executive order. The main source used for this study is the newspaper Correio do Povo, representative of the liberal-conservative sectors in southern Brazil.